2020
DOI: 10.1177/0300060520940455
|View full text |Cite
|
Sign up to set email alerts
|

NLRC5 alleviated OGD/R-induced PC12-cell injury by inhibiting activation of the TLR4/MyD88/NF-κB pathway

Abstract: Objective To assess the role of NOD-like receptor C5 (NLRC5; a major NLRC family protein that regulates immunity, inflammation and tissue fibrosis), in cerebral ischemia-reperfusion injury, characterized by inflammation and oxidative damage. Methods Blood NLRC5 levels were assessed in neonates with cerebral ischemia and in healthy controls. A stable PC12 cell line was established that overexpressed or knocked down NLRC5. Inflammatory responses, apoptosis rate and oxidative damage in PC12 cells under oxygen-glu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 35 publications
(41 reference statements)
0
9
0
Order By: Relevance
“…In the NLRC5-knockout and -knockdown cardiac muscle cells challenged with LPS, no obvious effect was observed for ROS production [ 61 ]. However, overexpression of NLRC5 caused significant decrease in ROS levels [ 62 ], and NLRC5 silencing was associated with increased ROS levels under oxygen-glucose deprivation/reperfusion (OGD/R) [ 63 ]. The exact mechanism of NLRC5 on the regulation of ROS generation remains to be clarified.…”
Section: Oxidative Stress Mediated By Prr-dependent Pathwaysmentioning
confidence: 99%
“…In the NLRC5-knockout and -knockdown cardiac muscle cells challenged with LPS, no obvious effect was observed for ROS production [ 61 ]. However, overexpression of NLRC5 caused significant decrease in ROS levels [ 62 ], and NLRC5 silencing was associated with increased ROS levels under oxygen-glucose deprivation/reperfusion (OGD/R) [ 63 ]. The exact mechanism of NLRC5 on the regulation of ROS generation remains to be clarified.…”
Section: Oxidative Stress Mediated By Prr-dependent Pathwaysmentioning
confidence: 99%
“…Activated caspase-1 promotes proteolysis and maturation of the pro-inflammatory cytokines IL-1b and IL-18, stimulating the occurrence of pyroptosis (38). It has been reported that inflammasome activation is associated with a variety of brain diseases, including ischemic and traumatic brain injury and neurodegenerative diseases (12,39,40). Co-immunoprecipitation experiments revealed that NLRC5 directly binds to the NLR family PYD containing 3 (NLRP3) and apoptosis-associated speck-like protein containing CARD (ASC), which is considered to be an activator and synergetic component of the inflammasome (41).…”
Section: Nlrc5 Activates Inflammasomesmentioning
confidence: 99%
“…Thus, NLRC5 may serve as an effective target for the treatment of cerebral I/R injury. Furthermore, Zhang et al found that the expression of NLRC5 in neonates with cerebral ischemia and OGD/R-induced PC12 cells was significantly reduced (12). However, NLRC5 overexpression was found to suppress the levels of inflammatory cytokines such as TNF-a, IL-6, IL-1b, ROS, malondialdehyde (MDA), Bax, and caspase-3, as well as apoptosis.…”
Section: Cerebral I/r Injurymentioning
confidence: 99%
See 2 more Smart Citations